Numerical Simulation of Synthetic Aperture Radar Images for Ocean Oil Spill Pollution. Issue 1 (2nd January 2016) - Yang, Wei; Qi, Cong-Hui; Zhao, Zhi-Qin
ABSTRACT: In order to study the scattering mechanism of oil spill pollution and the impacts on synthetic aperture radar images, both the computational modeling and its inverse problem are explored. The forward–backward iteration method and some optimization techniques are proposed to simulate the electromagnetic scattering from extra-large-scale sea surfaces. The local iteration methodology is first proposed to reduce the computational complexity to the order of rather than in terms of the nearly planar structure of the sea surface; therefore, the proposed method can effectively collect the massive backscattered data from the oily, polluted sea surface. Finally, based on the simulated data, the dual-polarization synthetic aperture radar images of the oil spill sea surface are studied for various conditions of sea states, radar polarizations, frequencies, and incidence angles.